Hak Asasi Manusia dan Relasi Keluarga dalam Islam: Tafsir Kontekstual terhadap Teks-Teks Hukum Keluarga - Rahmad Setyawan; Muhammad Asyrofudin (Human Rights et Justicia, 2025)
Social developments and modern family dynamics demand an understanding of Islamic family law that is responsive, humanistic, and in line with human rights principles. However, several provisions in family law texts still reflect normative constructions that are potentially discriminatory, particularly regarding husband-wife relations, divorce, and the protection of women’s and children’s rights. This study aims to analyze family relations in Islam through contextual interpretations of family law texts, emphasizing their relationship to human rights principles. This study is a normative-qualitative study with a multidisciplinary approach that combines various interpretations, the maq?sid as-Syar?‘ah framework, and a human rights perspective as a normative-critical instrument. Data were collected through a literature review of primary legal materials, namely the Qur’an and hadith related to family relations, as well as secondary legal materials in the form of classical and contemporary interpretations, human rights literature, and scientific journal articles relevant to the research issue. Then, they were analyzed thematically and hermeneutically contextually. The research findings show that a contextual interpretation based on human rights has significant implications for establishing just and equal family relations, particularly regarding husband-wife relations, divorce, and the protection of women’s and children’s rights. This interpretation encourages the development of partnership-based family relations, where husband and wife are positioned as legal subjects with equal rights and obligations, and ensures that divorce procedures are implemented fairly and responsibly. Furthermore, a contextual interpretation based on human rights also strengthens the guarantee of protection for the rights of women and children as groups often in vulnerable positions, both in the domestic sphere and in judicial practice. This emphasizes that the principles of justice, equality, and protection for all family members, especially groups often in vulnerable positions, are fundamental principles that must be the foundation of family law practice.